Perspectivas de la protección social ante el COVID-19: Próximos desafíos - Aline Peres; Roberta Brito; Charlotte Bilo; Mariana Balboni (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
– In 2020, the extensive consequences of the COVID-19 crisis placed social protection even more squarely at the centre of attention. As the health, economic and social impacts of COVID-19 echoed all over the world, social protection programmes were urgently developed, adapted, or extended to support those most affected. In celebration of socialprotection.org's 5-year anniversary, a global online event took place focusing on the global health crisis. This issue of Policy in Focus delves more in depth into the main topics discussed during the round tables, such as financing, universal basic income, linkages to food security and employment, as well as gender-, child-, and disability-sensitive programmes, among others. All articles were written by panellists and/or organisers of the conference.
Keywords: 330